2020
DOI: 10.1002/cpmc.119
|View full text |Cite
|
Sign up to set email alerts
|

An Exonuclease V–qPCR Assay to Analyze the State of the Human Papillomavirus 16 Genome in Cell Lines and Tissues

Abstract: Integration of the human papillomavirus (HPV) genome into host cell chromosomes has been observed in a majority of HPV-positive cervical cancers and a subset of oral HPV-associated cancers. HPV integration also occurs in long-term cell culture. Screening for HPV integration can be labor intensive and yield results that are difficult to interpret. Here we describe an assay based on exonuclease V (ExoV/RecBCD) and quantitative polymerase chain reaction (qPCR) to determine if samples from cell lines and tissues c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…If there were a general level of increased integration, DNA would be integrated in millions of different sites and would not generate detectable signals on Southern blots. We used a recently developed technique that uses exonuclease-resistant DNA as a measure of episomal status to determine whether mutation of E2 S23 alters the episomal/integrated status of the HPV16 genomes ( 87 89 ). In this assay, DNA is treated with TV exonuclease (Exo) which degrades linear DNA, but not circular.…”
Section: Resultsmentioning
confidence: 99%
“…If there were a general level of increased integration, DNA would be integrated in millions of different sites and would not generate detectable signals on Southern blots. We used a recently developed technique that uses exonuclease-resistant DNA as a measure of episomal status to determine whether mutation of E2 S23 alters the episomal/integrated status of the HPV16 genomes ( 87 89 ). In this assay, DNA is treated with TV exonuclease (Exo) which degrades linear DNA, but not circular.…”
Section: Resultsmentioning
confidence: 99%
“…3H ). To further characterize the status of the genomes in these cells we used TV exonuclease assays (this assay is based on the fact that episomal HPV16 genomes are resistant to exonuclease digestion) ( 58 , 59 ). This assay demonstrated that the viral DNA in the immortalized donor cell lines retained a predominantly episomal status, irrespective of whether the viral genomes were wild-type or HPV16(-p53) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because exonuclease V specifically digests linear DNA but not circular DNA, circular HPV genome can be amplified with a pair of divergent primers within L1 gene ( Table 1 ) from DNA treated with exonuclease V. The circular form of HPV genome was detected in cervical cancer tissue as shown in Figure 4 , suggesting that the 11.54 kb-long concatemeric HPV sequence revealed by nanopore sequencing could be an intermediate product during the rolling circle replication of HPV genome. To further determine the physical status of the HPV genome in the cancer tissue, we tested the resistance percentage of E2 and E6 to exonuclease V digestion, followed by qPCR ( Myers et al, 2019 ; Myers et al, 2020 ). Results showed that the average resistance of E2 and E6 to exonuclease V was in the range of 0.2–0.4 ( Figure 4 ; Table 2 ), while the average resistance of β-actin to exonuclease V was almost 0, which suggests that integrated and episomal HPV genome coexist in the cervical cancer tissue.…”
Section: Resultsmentioning
confidence: 99%